Parent-child conversations in three urban middle-class contexts: Mothers and fathers reminisce with their daughters and sons in Costa Rica, Mexico, and Germany - Schröder, Lisa (2013)
Abstract. The present study investigated culture- and gender-differences in mother- and father-child reminiscing with 3-year old daughters and sons in urban middle-class families from Costa Rica, Mexico, and Germany. Families of the three contexts were overall similarly elaborative and children contributed a similar amount of memory elaborations. However, context specific use of different elaborative elements related to specifi c elaborative styles. Compared to the Latin American families, conversations in German families were least socially oriented. Across contexts, parents talked more about social aspects with daughters than with sons. Costa Rican mothers and fathers were equally elaborative, whereas German and Mexican mothers were more elaborative than fathers. We found similarities but also specifi cities in parent-child conversations about the past across these contexts with similar educational backgrounds.Resumen. El presente estudio investigó diferencias según cultura y género en las conversaciones sobre el pasado de niños y niñas de 3 años de edad con sus progenitores en contextos urbanos en Costa Rica, México y Alemania. En los tres contextos, el nivel de elaboración general de las conversaciones fue similar y los niños produjeron una cantidad similar de recuerdos. Sin embargo, se encontraron diferencias culturales en algunos aspectos de elaboración. En comparación con las familias latinoamericanas, las conversaciones de las familias alemanas estaban orientadas socialmente en menor medida. En todos los contextos, los progenitores hablaron más acerca de aspectos sociales con las hijas que con los hijos. Padres y madres costarricenses evidenciaron niveles de elaboración similares, mientras que las madres alemanas y mexicanas mostraron niveles de elaboración mayores que los padres. Nuestros hallazgos indican la presencia de similitudes y diferencias en las conversaciones sobre el pasado en familias con niveles educativos similares provenientes de distintos contextos culturales.